2023
DOI: 10.1111/jsr.13863
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sleep deprivation and a low dose of ketamine on sleep and the electroencephalogram in Brown Norway rats

Abstract: SummaryKetamine is known for its antidepressant effects, but the mechanism underlying this effect remains largely unclear. In contrast to most antidepressant drugs, the action of ketamine is rapid, suggesting a different mode of action. A rapid antidepressant effect is also observed following sleep deprivation (SD). In the present study, we aimed to evaluate the effect of a 6‐h SD and acute ketamine treatment on vigilance states, locomotor activity, and electroencephalogram (EEG) power density spectra in Brown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Earlier it was also shown that racemic ketamine treatment (15, 25, and 50 mg/kg i.p.) increases EEG delta power during NREM sleep in rats ( Feinberg and Campbell, 1993 ; Wang et al, 2023 ). This is similar to our findings with (S)-ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier it was also shown that racemic ketamine treatment (15, 25, and 50 mg/kg i.p.) increases EEG delta power during NREM sleep in rats ( Feinberg and Campbell, 1993 ; Wang et al, 2023 ). This is similar to our findings with (S)-ketamine.…”
Section: Discussionmentioning
confidence: 99%